Dentists' actions about oral health of individuals with Down Syndrome - Ana de Lourdes Sá Lira; Claudio Inácio Reis Silva; Sylvana Thereza de Castro Pires Rebelo (Universidade Estadual de Campinas, 2016)
Aim: To investigate the knowledge and actions of dentists for treatment of individuals with Down syndrome. Methods: A questionnaire was applied to all the dentists (n=90) working at the FHS (Family Health Strategy) modules in the urban limits of Parnaíba, PI, Brazil. Four of the questions in the questionnaire were written according to the Theory of Planned Behavior Table and Likert scale (questions 6,7,9 and 15), in order to analyze the professionals' intentions. Sixteen objective questions were elaborated with the purpose of collecting information about the degree of the dentists' knowledge as regards the intention of attending courses in the patients with special needs area including DS, and interaction with other professionals and families. The option was to use a questionnaire applied to the dentists of the region, from August to November 2014. Results: It was found that most professionals were women and they considered themselves able to identify these patients. Among the professionals, 70% showed they had no difficulty in identifying the patient with DS, and 5.2% had no opinion about the subject. Only 6.6% of the professionals showed to be certain about their aptitude to attend to these patients; 70% were partially apt, that is, they were not absolutely sure about their aptness. There was a statistical relationship between the variables understanding and difficulty in the treatment. There was no statistical relationship between the variable capacity to identify, understanding of the needs and fitness variable in attendance. Conclusions: Patients with Down syndrome need more attention and care of dentists, they must also be involved in a multidisciplinary approach. Most of the professionals do not follow the procedures laid down by the Ministry of Health, but showed interest in attending a course in this area and there is a low number of SD patients being cared in Parnaíba, PI.